An Aquaculture Water Checker–design and Manufacture - Anh, Nguyen Tuan; Cu, Dang Xuan; Bao, Phung Quoc; Phi, Vu Anh; Duong, Bach Gia (Communications in Physics, 2012)
A real-time, mobile aquaculture water checker is presented. The configuration of double integrating spheres is developed for simultaneously measuring backward scattering R_d, forward scattering T_d and transmitted light T_c . Based on Kubelka-Munk model, a set of optical parameters including absorption coefficient μ _a , scattering coefficient μ_s and anisotropy g are calculated. The obtained results for diluted milk standard samples with different milk concentrations and aquaculture water samples with different densities of Psexdo-Nitzschia-delicatissium algae are also reported.